2020
DOI: 10.3390/v13010026
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Immune Profiling of Convalescent Plasma Donors Reveals Alterations in Specific Immune Subpopulations Even at 2 Months Post SARS-CoV-2 Infection

Abstract: Immune profiling of patients with COVID-19 has shown that SARS-CoV-2 causes severe lymphocyte deficiencies (e.g., lymphopenia, decreased numbers, and exhaustion of T cells) and increased levels of pro-inflammatory monocytes. Peripheral blood (PB) samples from convalescent plasma (CP) donors, COVID-19 patients, and control subjects were analyzed by multiparametric flow cytometry, allowing the identification of a wide panel of immune cells, comprising lymphocytes (T, B, natural killer (NK) and NKT cells), monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…Using flow cytometric analysis, our group first determined the relative frequencies of different immune cell subsets in the peripheral blood. We and others have previously shown cell subset frequencies remain altered into the convalescent phase after SARS-CoV-2 infection ( 1 , 8 ), but few reports comprehensively address whether this persists into late convalescence or is associated with PASC. Here, cell frequencies were reported as a frequency of the overall CD45 + population per each individual as done previously ( 1 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Using flow cytometric analysis, our group first determined the relative frequencies of different immune cell subsets in the peripheral blood. We and others have previously shown cell subset frequencies remain altered into the convalescent phase after SARS-CoV-2 infection ( 1 , 8 ), but few reports comprehensively address whether this persists into late convalescence or is associated with PASC. Here, cell frequencies were reported as a frequency of the overall CD45 + population per each individual as done previously ( 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…We next investigated longitudinal phenotypic differences in T cells between those experiencing persistent symptoms and those with resolved disease. Our group and others have observed T cell activation that persists into the early convalescent phase following SARS-CoV-2 infection ( 1 , 8 ), but few studies have investigated phenotypic differences into the intermediate and late phases of convalescence, particularly in individuals with prolonged symptom syndromes. One recent study observed longitudinal changes in T cell activation independent of ongoing symptoms ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, in the light on the complex immune dysregulation that occurs during acute infection (11,12), we hypothesize that COVID-19 could have long-term impact on immune functions, such as the ones observed in patients that experienced bacterial sepsis (13). Indeed, immune profiling of SARS-CoV-2 recovered patients indicates persistent changes in the phenotype of innate (monocytes and granulocytes) but most importantly in adaptive (T, B, and NKT) immune cells (14)(15)(16).…”
Section: Introductionmentioning
confidence: 97%
“…T cell immunity arises, as anticipated, during infection, and the quality and quantity of the same varies according to the intensity of disease. [31,48,51,63,65,67,68,70,74,89,91,93,94,98,102,[109][110][111].…”
Section: Correlations With Immunity or Protectionmentioning
confidence: 99%